Statistiscal truth - Bieligk, K.F.; Gibson, George (London : Hutchinson, 1942)
Bibliotheek Camille Huysmans
Dedicator: Bieligk, K.F., dedicatee: Huysmans, Camille
Engels
Brochure
Keywords: Weimarrepubliek; Verdrag van Versailles; herstelbetalingen; Duitsland